PSYCHOPATHOLOGY AND ALCOHOL ABUSE IN TEENAGERS - López Soler, Concepción; Freixinós Ros, Mª Angeles (Anales de Psicología / Annals of Psychology, 2001)
The purpose of this essay is to analyse the relationship between psychological disturbances and alcohol abuse in young people. In order to carry out this aim, we have worked with a sample of 324 teenager from Murcia, 167 boys and 157 girls. In order to evaluate the psychopathological disturbances in this sample, we have used the YSR (Youth Self Report). It showed 10 empirical syndrome, from which three of them can be categorised as internalising ( Depression / Anxiety – Factor I -, Somatic complain – Factor III -, Shyness – Factor V -), five as externalising (Search for attention – Factor IV - , Antisocial behaviour – Factor II - , Drug abuse / Disocial - Factor VI - , Hyperactivity – Factor VIII – and Delincuency – Factor X -) and finally, we also obtained the so called mixed ones (Problems of thinking – Factor VII - and problems of identity – Factor IX - ) The results shows a relationship between psychological disturbance and alcohol abuse, since 6 of the 10 empirical syndromes found in the sample, consumers get higher scores in the empirical syndrome than non consumers.